Biocultural approaches to sustainability: A systematic review of the scientific literature - Hanspach J; Haider LJ; Oteros-Rozas E; Olafsson AS; Gulsrud NM; Raymond CM; Torralba M; Martin-Lopez B; Bieling C; Garcia-Martin M; Albert C; Beery TH; et al. (WILEY, 2022)
1. Current sustainability challenges demand approaches that acknowledge a plurality of human-nature interactions and worldviews, for which biocultural approaches are considered appropriate and timely.
2. This systematic review analyses the application of biocultural approaches to sustainability in scientific journal articles published between 1990 and 2018 through a mixed methods approach combining qualitative content analysis and quantitative multivariate methods.
3. The study identifies seven distinct biocultural lenses, that is, different ways of understanding and applying biocultural approaches, which to different degrees consider the key aspects of sustainability science-inter- and transdisciplinarity, social justice and normativity.
4. The review suggests that biocultural approaches in sustainability science need to move from describing how nature and culture are co-produced to co-producing knowledge for sustainability solutions, and in so doing, better account for questions of power, gender and transformations, which has been largely neglected thus far.A free Plain Language Summary can be found within the Supporting Information of this article.A free Plain Language Summary can be found within the Supporting Information of this article.